Humidity Effects on Effective Elastic Properties of Rock: An Integrated Experimental and Numerical Study. Issue 8 (5th August 2019) - Hossain, M. Manzur; Arns, Ji‐Youn; Liang, Zhirong; Chen, Zhixi; Arns, Christoph H.
Abstract: The surface energy of minerals increases due to a loss of humidity. In rocks this leads to strains without applying external stress (stress‐free strain) and affects the rocks' elastic response. We utilize finite element calculations on X‐ray micro‐CT images to analyze the extreme cases of surface energy contributions and no surface energy contributions for the small strain case. Including surface energy utilizing published surface energies of quartz significantly increases the simulated bulk modulus. Grain contacts are considered perfectly cemented and therefore do not contribute to this difference. Confining pressure is not applied in the experiment to estimate the impact of surface energy to avoid the effect of grain contact slippage due to different stress paths. In addition, we compare simulated moduli with experimentally determined parameters. In this case, we incorporate confining pressure in the experiment since grain contacts are not considered in the simulation. The main reason to use confining pressure in the experiment here is to close the grain contacts with a view that the resulting porosity reduction is negligible. Key Points: The impact of humidity on effective elastic properties of Bentheimer sandstone is determined using experiments at ambient confining pressure Simulated moduli are compared with experimentally determined parameters Digital rock physics is utilized to show that a major component of the difference in measured elastic moduli can be attributed to the impact of surface energy